Rebitagem por fricçao de alumínio 2024-T351 em policarbonato - Rodrigues, Camila Fernanda (2014)
This dissertation addressed the feasibility study of Friction Riveting technique on polycarbonate and 2024-T351 aluminum alloy spot joints. Design of experiments and Artificial Neural Network modelling were used to investigate the influence of process parameters on mechanical and microstructural properties of joints. These joints were produced at the Institute for Research Helmholtz Zentrum Geesthacht (HZG), in Germany, during the undergraduate years of the applicant. Process temperature was measured using an infrared camera. The mechanical properties of the joints were determined by tensile testing. The macro and microstructural characterization were carried out by light optical microscopy (LOM) and Vickers microhardness tests. The fracture mechanisms were investigated by optical and scanning electron microscopy (SEM). The level of PC degradation in the joining area was obtained by viscometry and Fourier transform infrared spectroscopy (FTIR). The average peak temperatures meausured during joining varied between 52% and 72% of the melting point interval of AA 2024 aluminium alloy. Strong joints with high anchoring efficiency were achieved, with ultimate tensile strength of approximately 90% of metallic rivet, and non-catastrophic ductile fracture at the metallic rivet outside the joined area. This is desirable failure type in riveted polymeric structures and an indication of high-strenght joints. The viscometry and FTIR analysis showed the absence of thermal degradation of the PC in the riveted joint. Statistical and Artificial Neural Networks modeling process showed good repeatability and reproducibility within the conditions studied. These results demonstrated the feasibility of producing spot joints of rivets 2024-T351 and PC by using the FricRiveting process.